Determinants of animal behaviour - Cartwright, Jo-Anne, 1955- (Routledge modular psychology., 2002)
A concise introduction to psychological theories which attempt to explain non-human animal behaviour. Theories covered include evolutionary explanations, classical and operant conditioning and social learning.